Multi-use naked barley: A new frontier. (November 2021) - Meints, Brigid; Vallejos, Cristiana; Hayes, Patrick
Abstract: Barley ( Hordeum vulgare ) is one of the oldest known domesticated crops and the fourth most widely grown cereal crop in the world. Barley has three principal end-uses: feed, food, and malt. Each end-use of barley requires different characteristics, but hull adherence and beta-glucan content are important for each of the three classes. Naked (hull-less) barley, which threshes freely from the hull, makes up a very small percentage of overall barley production and is mainly grown for food end-uses. However, naked barley shows potential as a crop that can be used for multiple end-uses. This review will describe the progression of naked barley in the US as well as ongoing research at Oregon State University. With the genetic resources from around the world that are available in germplasm repositories and continued research on end-use quality, advances can be made to create a new frontier of naked barley for multiple end-uses that will benefit growers, processors, and consumers. Graphical abstract: Image 1 Highlights: Naked currently makes up a very small percentage of overall barley production. Naked barley shows potential as a crop that can be used for multiple end-uses. This paper describes the progress of naked barley in the US and ongoing research. Advances can be made to create new naked barley varieties for multiple end-uses.